2017
DOI: 10.3389/fpsyg.2017.02093
|View full text |Cite
|
Sign up to set email alerts
|

Restoration and the City: The Role of Public Urban Squares

Abstract: Over recent decades, the study of psychological restoration has attracted a considerable amount of interest within and without the boundaries of environmental psychology, with most of the work focused on analyzing restoration in natural contexts. However, little attention has been paid to the (possible) restorative potential of urban settings, as they have usually been expected not to be restorative and to present some elements that might imply negative health outcomes in the short and long term. In this field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 70 publications
2
47
0
3
Order By: Relevance
“…In agreement with other studies [6,10,11,14,19,20], the results reported here confirm the initial study hypothesis that some urban places exert a positive impact on people’s well–being and quality of life. Thus, the present study has demonstrated a positive effect that reflects the emotionally restorative capacity of the urban places analysed, whereby environmental experiences in these places yielded a statistically significant reduction in perceived stress and the negative emotions of sadness and anger, and a trend towards an increase in the positive emotions of happiness and calm.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with other studies [6,10,11,14,19,20], the results reported here confirm the initial study hypothesis that some urban places exert a positive impact on people’s well–being and quality of life. Thus, the present study has demonstrated a positive effect that reflects the emotionally restorative capacity of the urban places analysed, whereby environmental experiences in these places yielded a statistically significant reduction in perceived stress and the negative emotions of sadness and anger, and a trend towards an increase in the positive emotions of happiness and calm.…”
Section: Discussionsupporting
confidence: 93%
“…There is thus a need to extend research on restorative environments to urban settings in order to determine whether these may also be considered restorative, as some recent studies would seem to suggest [18]. The results of one recent study revealed that participants’ psychological state improved after spending half an hour in one of two selected urban squares [19,20]. Visitors to both squares showed better cognitive performance, reduced negative affect variables (tension-anxiety, anger-hostility, fatigue and stress) and reported an increase in happiness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…San Juan et al 50 compared 2 open public squares, which were either high in natural elements and high in enclosure or low in natural elements and low in enclosure. They found that both squares decreased tension-anxiety, anger-hostility, fatigue, vigor, and stress, and increased happiness from pre- to posttest.…”
Section: Empirical Research On Urban Componentsmentioning
confidence: 99%
“…The theories and the majority of the applied research on restorative environments have focused on examining natural settings (Ulrich, 1983, Kaplan & Kaplan, 1991San Juan, Subiza-Pérez, & Vozmediano, 2017). The restorative potential of built urban settings has been largely ignored, and often unpleasant urban scenes have been chosen merely to highlight the restorative qualities of nature (Karmanov & Hamel, 2008;San Juan et al, 2017). As recent evidence suggests that urban settings can also be restorative (Stigsdotter et al, 2017), there is a need to evaluate whether they provide restoration on similar aspects as natural settings.…”
Section: Introductionmentioning
confidence: 99%